Alleviation of aqueous nitrogen loss from paddy fields by growth and decomposition of duckweed (Lemna minor L.) after fertilization. (January 2023) - Wang, Yuan; Chen, Xiaodong; Guo, Bin; Liu, Chen; Liu, Junli; Qiu, Gaoyang; Fu, Qinglin; Li, Hua
Abstract: Runoff loss of nitrogen from paddy fields has received increasing attention in recent years. Duckweed is an aquatic plant frequently found in paddy fields. In this study, the effects of duckweed ( Lemna minor L.) in floodwater on aqueous nitrogen losses from paddy fields were systematically investigated. Results demonstrated that the growth of duckweed decreased total nitrogen concentrations in floodwater and nitrogen runoff loss from paddy fields by 16.7%–18.3% and 11.2%–13.6%, respectively. Moreover, compared with NO3 −, NH4 + was preferentially removed by duckweed. 15 N isotope tracer experiments revealed that the growth and decomposition of duckweed acted as a "buffer" against the nitrogen variation in floodwater after fertilization. During the growth of duckweed, leaves were found to be the principal organ to assimilate NH4 + and release NO3 − by using non-invasive micro-test technology. Duckweed degradation increased the content of hydrophobic acids and marine humic-like substances in floodwater, which promoted the migration of nitrogen from floodwater to soil. Redundancy analysis and structural equation models further illustrated that pH and temperature variation in floodwater caused by duckweed played a greater role in aqueous nitrogen loss reduction than the nitrogen accumulation in duckweed. This study suggested that the growth of duckweed in paddy fields was an effective supplementary method for controlling aqueous nitrogen loss during agricultural production. Graphical abstract: Image 1 Highlights: Duckweed lowered N content in floodwater and N runoff losses from paddy fields. NH4 + in floodwater was preferentially assimilated by the leaves of duckweed. PH and temperature variation caused by duckweed affected aqueous nitrogen loss. Duckweed decomposition products contributed to N transfer from floodwater into soil. Duckweed reduced nitrogen variation after fertilization and increased rice yields.